Perceived value and its relationship to satisfaction and loyalty in cultural coastal destinations: a study in Huanchaco, Peru - Regalado-Pezúa, Otto; Carvache-Franco, Mauricio; Carvache-Franco, Orly; Carvache-Franco, Wilmer (PLOS, 2023)
Coastal tourism offers a wide variety of activities related to nature and culture in a sustainable environment. The present study in a coastal destination with cultural characteristics aims to (i) establish the dimensions of perceived value, (ii) determine the relationship between perceived value and satisfaction, and (iii) identify the relationship between perceived value and loyalty in variables such as return, recommendation, and word of mouth in a cultural coastal destination. This quantitative research used a sample of 384 valid questionnaires collected in Huanchaco, Peru, a city next to the Pacific Ocean, being a coastal destination with cultural potential. Factor analysis and multiple regression were applied for data analysis. The results show three dimensions of value perceived by tourists in coastal destinations: emotional and social value, economic value, and functional value. Of these, emotional and social value is the most salient predictor of tourist satisfaction and loyalty. These results will serve as management guides for cultural coastal destination managers and contribute to the academic literature.
Keywords: Tourism; Customer satisfaction; Turismo; Loyalty; Satisfacción del cliente; Peru; Lealtad; Perú; Coast Region; Región de la costa; https://purl.org/pe-repo/ocde/ford#5.02.04